Evaluation of rest-ingestion index in a food and nutrition unit of a university restaurant (Research, Society and Development, 2023)
The rest/intake index (IR/I) is an indicator commonly used in Food and Nutrition Units to verify consumer satisfaction with the menu offered and to assess food waste. With this, the objective of this work is to evaluate the rest-intake in a food and nutrition unit of a university restaurant. This is an observational, quantitative and descriptive study, carried out at the UAN of the UFRN University Restaurant. Data on food waste from the central unit's clientele referred to the period from May to July 2022. The results showed an average rest-intake index, in the months of May, June and July of 7.03%, 7.95% and 7.11% respectively, which is classified as good. This satisfactory result can be associated with some strategies that the place already carries out, such as annual campaigns against waste, evaluation of daily acceptance of the preparations served and standardization of the way of preparation through the use of technical sheets. However, despite the rest-intake index percentages being considered satisfactory on most days, there is still a need for measures for improvement since there were some days that were high. This demonstrates that interventions in relation to the production process of the menus executed in the UK must be intensified, requiring supervision of the faithful execution of the preparation technical sheets, review of gastronomic and culinary techniques, in addition to raising awareness among handlers, as well as Education measures Food and Nutrition with diners.